Reading graphic design history image, text, and context - Raizman, David (Bloomsbury Visual Arts, 2021)
Reading Graphic Design History uses a series of key artifacts from the history of print culture in light of their specific historical contexts. It encourages the reader to look carefully and critically at print advertising, illustration, posters, magazine art direction and typography, often addressing issues of class, race and gender.David Raizman's innovative approach intentionally challenges the canon of graphic design history and various traditional understandings of graphic design. He re-examines'icons'of graphic design in light of their local contexts, avoiding generalisation to explore underlying attitudes about various social issues. He encourages new ways of reading graphic design that take into account a broader context for graphic design activity, rather than broad views that discourage the understanding of difference and the means by which graphic design communicates cultural values. With a foreword by Steven Heller.